2014
DOI: 10.1093/mnras/stu1924
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for a low-mass black hole in SWIFT J1753.5−0127

Abstract: The black hole (BH) candidate SWIFT J1753.5-0127 has remained active since the onset of its 2005 outburst. Emission lines in the optical spectrum were observed at the very beginning of the outburst, but since then the spectrum has been featureless making a precise BH mass estimation impossible. Here we present results from our optical and ultraviolet (UV) observations of SWIFT J1753.5-0127 taken in 2012-2013. Our new observations show extremely broad, double-peaked emission lines in the optical and UV spectra.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 73 publications
4
60
2
Order By: Relevance
“…The distance of Swift J1753.5-0127 is poorly constrained, but likely lies somewhere between 2.5−10 kpc (Cadolle Bel et al 2007;Zurita et al 2008). Recent optical observations suggest that the binary consists of a low-mass BH and a somewhat evolved 0.2 M companion star (Neustroev et al 2014). We adopt i = 40…”
Section: Swift J17535-0127mentioning
confidence: 99%
“…The distance of Swift J1753.5-0127 is poorly constrained, but likely lies somewhere between 2.5−10 kpc (Cadolle Bel et al 2007;Zurita et al 2008). Recent optical observations suggest that the binary consists of a low-mass BH and a somewhat evolved 0.2 M companion star (Neustroev et al 2014). We adopt i = 40…”
Section: Swift J17535-0127mentioning
confidence: 99%
“…Examples of the application of this technique to the real data are given in Neustroev (1998), Neustroev et al (2002Neustroev et al ( , 2014. References.…”
Section: Accretion Disc Parameters From Modelling Of the Emission-linmentioning
confidence: 99%
“…BHC Swift J1753.5-0127 has a short orbital period of 3.2 ± 0.2 hrs (Zurita et al 2007). However Neustroev et al (2014) suggested the orbital period is 2.85 hrs. They also reported that the binary has a primary BH mass of less than 5 M ⊙ and companion as 0.17−0.25M ⊙ and disk inclination angle of > 40…”
Section: Introductionmentioning
confidence: 99%